ANALISIS PELAKSANAAN FULL DAY SCHOOL DI SMA NEGERI 06 PONTIANAK - Noviarti, Dina; Aminuyati, Aminuyati; Sumartomo, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the implemtation of Full Day School at SMAN 06 Pontianak.Based on Full Day School indicators namely,optimizing the use of time,intensifying talent depelopment,instilling the importance of the procces,focusing on learning,developing creativity and well controlled children.Data collection techniques used are observation,interview and documentation.This analysis is presented in a qualitative descriptive manner using 1 informant as principal,2 teachers and 4 students.Based on the results of interviews and observations that are carried out based on Full Day School indicators,1.optimizing the use of time is quite good where all activities are scheduled but there are obstacles in sports subjects that are still scheduled at noon due to lack of sports teacher.2.Intensive exploring and developing talent is categorized quite well with the existence of extracurricular choices.3.instill the importance of the process categorized quite well the results of the study indicate that systematic scheduled learning activities.4.focus on student learning is categorized as not good that the concentration of students when learning is easily disturbed,especially in the afternoon.5. developing creativity in using innovative learning methods is said to be very lacking because teachers still use the old methods.6.children can be controlled well shows that the school can not fully control students.The advice in this research is for school to pay more attention to schoolfacilities and infrastructure,teacherr are expevted to be able ti innovate in delivering learning and for students to be more enthusiastic in learning.Keywords: Full Day, Full Day School, Full Day School Implementation